2017
DOI: 10.1038/s41598-017-01810-4
|View full text |Cite
|
Sign up to set email alerts
|

Distinct mechanisms of acquisition of mcr-1 –bearing plasmid by Salmonella strains recovered from animals and food samples

Abstract: Since the report of its discovery in E. coli in late 2015, the plasmid-mediated colistin resistance gene, mcr-1, has been detected in various bacterial species in clinical setting and various environmental niches. However, the transmission mechanisms of this gene in Salmonella is less defined. In this study, we conducted a comprehensive study to characterize the genetic features of mcr-1-positive Salmonella strains isolated from animals and foods. Our data revealed that Salmonella recovered from animals and fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Among them, 9, 8, 8, and 7 isolates were resistant to tetracycline, cefotaxime, ciprofloxacin, and florfenicol respectively, but all were susceptible to imipenem ( Table 2 ). Mcr-1 is usually found to coexist with other resistance genes (extended-spectrum β-lactam, floR , and tet (A)) in bacteria [ 42 , 43 , 44 ]. In this study, 6, 5, 5, and 2 of the nine mcr-1 -bearing E. coli isolates harbored floR , bla CTX-M , bla TEM-1, and tet (A) genes, respectively ( Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Among them, 9, 8, 8, and 7 isolates were resistant to tetracycline, cefotaxime, ciprofloxacin, and florfenicol respectively, but all were susceptible to imipenem ( Table 2 ). Mcr-1 is usually found to coexist with other resistance genes (extended-spectrum β-lactam, floR , and tet (A)) in bacteria [ 42 , 43 , 44 ]. In this study, 6, 5, 5, and 2 of the nine mcr-1 -bearing E. coli isolates harbored floR , bla CTX-M , bla TEM-1, and tet (A) genes, respectively ( Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Salmonella strains that acquire multidrug resistance genes would be difficult to treat and would result in an even higher number of cases with severe morbidity and high frequency of mortality. After Salmonella species carrying mcr-1 were detected in the United Kingdom in 2016, the level of occurrence of mcr-1 in Salmonella among livestock and humans, but also the environment, is increasing worldwide ( Cui et al, 2017 ; Yi et al, 2017b ). In addition, although another five mcr variants ( mcr-2 , mcr-3 , mcr-4 , mcr-5 , and mcr-9 ) have been identified in Salmonella species ( Carattoli et al, 2018 ; Garcia-Graells et al, 2018 ; Borowiak et al, 2019 ; Carroll et al, 2019 ; Sun et al, 2020 ), mcr-1 is still the most common mcr gene found in COL-resistant Salmonella spp.…”
Section: Introductionmentioning
confidence: 99%
“…For example, while plasmids that carry mcr-1 in Salmonella food isolates were conjugative, plasmids in Salmonella animal isolates were not. It was suggested that mcr-1 acquisition in food Salmonella isolates probably due to a cross species conjugation from E. coli, instead of Salmonella animal samples (Cui et al, 2017). (Li et al, 2016;Zeng et al, 2016;Zurfuh et al, 2016), Carbapanemases (Sun et al, 2016), and New Delhi Metallo β-Lactamase (bla NDM-5 , bla NDM-9 ) (Borowiak et al, 2017;Yao et al, 2016).…”
Section: Resultsmentioning
confidence: 99%